Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Baniah Rahmat Utama - Gunandi, Iwan; Amidi; Kalsum, Ummi (PT Maju Malaqbi Makkarana, 2025)
This study aims to determine the Influence of Work Motivation and Work Discipline on Employee Performance at PT. Baniah Rahmat Utama. The sample used in this study was 100 respondents. The data used in this study are primary and secondary data. The data analysis used is qualitative and quantitative analysis. The analysis technique used is multiple linear regression. The results of the multiple linear regression analysis show that work motivation and work discipline have a positive effect on employee performance. The results of the simultaneous hypothesis test show Fcount, meaning that there is a significant influence of work motivation and work discipline on employee performance. The results of the partial hypothesis test show the tcount value of work motivation, work discipline, meaning that partially there is a significant influence of work motivation and work discipline on employee performance. The determination value shows that work motivation and work discipline can contribute to the rise and fall of employee performance, with the magnitude of the change caused by 76.8%.